Pemilihan Informasi terhadap Risiko Produksi Usahatani Padi Sawah - Widiya, Widiya; Nurliza, Nurliza (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The agricultural sector, particularly rice farming, is a primary source of food and income. However, rice farming faces various challenges in increasing productivity due to the limited awareness of the important role of information related to production. The aim of the research is to analyze the selection of information regarding production risks in rice farming. The research method is a sequential mixed method involving 96 rice paddy farmers. Data analysis using structural equation modeling (SEM) with SMART PLS 3.0 software. The research results indicate that the selection of information, which includes information quality, information benefits, and information sources, significantly affects the management of production risks. Meanwhile, information costs have an insignificant impact on managing production risks in rice farming. Therefore, the government and related institutions need to improve access to quality information that is beneficial and from trustworthy sources. More frequently hold training and outreach programs so that farmers become more active and aware of the importance of information, enabling them to continuously seek information to improve the quality of their decision-making.